The environmental holistic formation in the students that get ready to impart classes of Biology in the secondary education in Cuba - Yunior Ramón Velázquez-Labrada; Eumelia Victoria Romero-Pacheco; Luis Roberto Jardinot-Mustelier (Maestro y Sociedad, 2016)
Current environmental problems are becoming more serious and cause great concern to all humanity. It is necessary to encourage a teacher who understands the proper role play as an integral part of the environment, for which must have integrated biological, geographical and environmental knowledge chemical content. That is why in Cuba, there is an environmental policy governed by normative documents and is the responsibility of the environmental education of new generations schools. This work offers a way to contribute to the holistic environmental education in students preparing to teach biology in high school in Cuba. actions to be taken from the substantive processes university are proposed.